Fine structural analysis of solvent activated Cu-BTC for carbon dioxide capture - Chowdhury, S. (Trans Tech Publications Ltd, 2014)
Metal organic frameworks (MOFs) are presently under substantial investigation due to their properties and high potential as new class of porous material for carbon dioxide (CO2) capture. Experimentally, CuâBTC crystalline frameworks with diameter of approximately 6â13 Î¼m are found. The washing method of Cu-BTC is examined using three different solvent, (a) ethanol and water of 1:1 ratio, (b) water, and (c) acetone, to improve the BET surface area. These materials display approximately type I isotherms with no hysteresis and saturation. CO2 adsorption capacities study shows that acetone wash material can store about 5.98 mmol g-1of CO2 at 25 Â°C and 1.2 bars. Â© 2014 Trans Tech Publications, Switzerland.